감성 일치도 평가를 통한 화장품 용기 CMF 디자인 프로세스 검증 및 개선 - 류효연; Ryoo Hyo Yun; 김선아; Kim Sun Ah (기초조형학연구, 2019)
현재 시장에 나와 있는 화장품의 기능은 향상되고 있다. 이에 대해 소비자의 욕구가 높아짐에 따라 기업들은 감성 브랜딩으로 브랜드 경쟁력을 강화하고 있으며, 이를 위해 CMF 디자인을 구체적 도구로 활용하는 경우가 많다. 하지만 CMF 디자인 프로세스를 살펴봤을 때, 디자이너 및 개발자의 감성과 소비자의 감성이 일치하는지 확인하는 과정이 생략되어 있으므로 브랜딩 전략 또는 개발품의 성공 요소에 있어 CMF 디자인 요소의 세부적인 영향을 확인하기 어렵다. 따라서 본 연구의 목적은 A 기업의 클렌징 밤 제품을 기반으로 디자이너 및 개발자의 감성과 소비자의 감성이 일치하는지 알아보고, 그 일치성을 검증하는 평가 단계가 포함된 CMF 디자인 프로세스를 검증하는 것이다. 본 연구의 목적을 위해 먼저 문헌 조사를 통해 제품 디자인, 감성 브랜딩, CMF 디자인에 관한 이론적 고찰을 하였고, 제안된 CMF 프로세스를 따라 사례연구를 하였다. 제안된 프로세스는 리서치, 전략, 평가, 개발로 이루어져 있으며, 본 연구는 평가 단계까지 실시하였다. 리서치 단계에서는 트렌드 조사, 사례조사, 소비자 요구조사, 제품 속성 파악 등을 시행하였으며, 전략 단계에서는 페르소나 설정, 무드보드, 시각화를 시행하였다. 평가 단계에서는 감성 일치도 조사를 통해 평가의 필요성을 고찰하였다. 결과적으로 소비자의 감성과 디자이너 및 개발자의 감성은 다르게 도출되었으며, 소비자의 감성 언어적 측면에 있어 CMF 디자인 요소의 영향을 확인할 수 있었다. 끝으로, 본 연구를 통하여 실무자들이 성공적으로 브랜드를 강화하고 관리하는데 도움이 되고자 한다. The functions of cosmetics currently on the market are improving. In response, companies are strengthening their brand competitiveness with emotional branding, often using CMF designs as a concrete tool to do so. However, when looking at the CMF design process, it is difficult to identify the detailed impact of CMF design elements on branding strategies or the success factors of the product, since the process of ensuring that the sensibilities of designers and developers match those of consumers. Therefore, the purpose of this study is to verify the CMF design process, which includes an evaluation step that identifies the sensibility of designers and developers and verifies the consumer's sensibility based on Company A's cleansing products. For the purpose of this study, the theoretical considerations on product design, emotional branding, and CMF design were first made through literature research, and case studies were conducted in accordance with the proposed CMF process. The proposed process consists of research, strategy, evaluation, and development, and this study was conducted up to the evaluation stage. In the research phase, trend research, case study, consumer demand survey, and product attributes identification were conducted, and Persona, mood board, and visualization were performed during the strategy phase. During the evaluation phase, the need for evaluation was considered through an emotional concordance survey. As a result, consumer sensitivity and designer and developer sensitivity were derived differently, and the influence of CMF design elements in the language aspect of consumer sensitivity was identified. Finally, through this study, we hope to help practitioners successfully strengthen and manage their brands.